Efficacy of Self-Directed Learning in the Supracondylar Fracture Performance Improvement Module at an Academic Pediatric Orthopedic Institution - Eric W. Edmonds; John W. Kemppainen; Joanna H. Roocroft; John Munch; Tracey P. Bastrom (Advances in Orthopedics)
Maintenance of certification (MOC) within a medical society requires continuing medical education that demonstrates life-long learning, cognitive expertise, and practice-based self-assessment. This prospective study sought to evaluate whether a self-directed Practice Improvement Module (PIM) would improve pediatric orthopedic patient outcomes, thus demonstrating evidence of life-long learning (Part II MOC credit) in treating supracondylar humerus fractures. Six surgeons and 113 patients were included. There was no significant difference in actual fracture outcome before or after PIM at any level of surgeon experience regarding radiographic appearance or need for reoperation (p>0.10). Junior staff demonstrated a statistically significant improvement in the percentage of time that marking the operative site was documented in the chart by the surgeon before (38%) and after (65%) PIM (p=0.02). The self-directed education portion of the supracondylar fracture PIM led to modest improvement in documentation habits among junior staff, without impact on overall patient outcomes. Therefore, the PIM appears to be less useful in providing evidence for life-long learning as it relates to surgical outcomes (Part II MOC/CME), yet, it may directly benefit practice-based self-assessment (Part IV MOC), and the self-assessment and Personal Improvement Plan may be the most important portion of the PIM to improve outcomes.